2020
DOI: 10.3122/jabfm.2020.01.190230
|View full text |Cite
|
Sign up to set email alerts
|

Early-Career and Graduating Physicians More Likely to Prescribe Buprenorphine

Abstract: Using data from 2016 to 2018, we demonstrate a sharp increase in graduating family medicine residents and early-career family physicians who intend to or actually prescribe buprenorphine with no change in mid-to-late-career physicians. Family physicians are responding to the opioid crisis but, growing the family medicine workforce to treat opioid-use disorder will require a larger response from mid-to-late-career physicians. (J Am Board Fam Med 2020;33:7-8.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Results from this survey suggest that current primary care trainee physicians, who have trained during this historically devastating overdose crisis, are more inclined than primary care attending physicians to view OUD medications as effective and to express interest in working with this population and prescribing buprenorphine to treat OUD (McGinty et al, 2020). This aligns with data showing that a growing proportion of trainee physicians in family medicine are obtaining buprenorphine waivers (Peterson et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…Results from this survey suggest that current primary care trainee physicians, who have trained during this historically devastating overdose crisis, are more inclined than primary care attending physicians to view OUD medications as effective and to express interest in working with this population and prescribing buprenorphine to treat OUD (McGinty et al, 2020). This aligns with data showing that a growing proportion of trainee physicians in family medicine are obtaining buprenorphine waivers (Peterson et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…Studies have shown that early-career family physicians are leading this charge. 11 While some have advocated for requiring DATA 2000 waiver training during residency, it is not currently an ACGME requirement. [12][13] The American Academy of Family Physicians recommended curriculum guidelines for substance use disorders include treating patients with buprenorphine; however, they do not call for residents to obtain their waivers to prescribe it.…”
Section: Discussionmentioning
confidence: 99%
“…9 Furthermore, only 28.6% of family medicine residencies reported having a dedicated addiction medicine (ADM) curricula with a lack of faculty expertise listed as the top reason why many programs did not offer training in ADM. 10 Studies have also shown that few family physicians feel prepared to prescribe or are currently prescribing buprenorphine, which is the predominant medication used in office-based settings for opioid use disorder. [11][12][13][14] With a goal of increasing the workforce to address SUD, ADM became an American Board of Medical Specialties (ABMS)-recognized subspecialty in 2016 under the American Board of Preventive Medicine. 15,16 Any physician with an ABMS-recognized primary board certification is eligible to apply with appropriate fellowship training or, before 2025, sufficient addiction-focused practice experience.…”
Section: Introductionmentioning
confidence: 99%